Relato de caso - Realidade docente em processo multisseriado desenvolvido na zona rural do estado do Pará nos anos de 2015 e 2016. - Moreira, Cleisiane Lopes Moreira (Universidade Federal do Tocantins, 2023)
This paper describes a case report about teaching activities of multiseriate program, applied to students of Rural Area in Municipality of Novo Repartimento on state of Pará. Has objetive to describe how is reality of educational activity multisseriado and applied in the series of 1st to 5th and 6th and 7th year of elementary school. The work describ at difficulties and challenges find by teachers and students. The multi-seriado teaching developed brings to student more learning difficulties, since the teacher has as responsibility to teach in class to various series in the same room, and has work with the different levels of learning. The Teachers has responsible in addition to their classes, for doing school meals and cleaning at unit. The school structure was extremely precarious, the union community together with the teacher, maked to efforts for construction of a new school, improving the conditions of teaching learning of the school, bringing students a better school structure tand beter attendance conditions, consequently improving classes and teaching. Although there are many problems in this teaching process, the assisted community strives to keep it going, because ther'nt existen olther form to education in this region, thus demonstrating the fragility of basic education in our Country's Rural Zone.